Semi-automated method for the differential determination of plasma catecholamines - McCullough, Helen (1968)
A method is described for the estimation of adrenaline and noradrenaline in a 5 to 10 ml plasma sample. A batch technique of adsorption and elution from alumina is used and the final estimation is carried out using an automated fluorimetric technique based on the trihydroxyindole method. Fluorescence is stabilized first by thioglycollic acid to give noradrenaline concentrations only and then by ascorbic acid to give the total catecholamine concentration. The results of a number of catecholamine analyses are given.